How vergence influences the perception of being looked at. (November 2022) - Linke, Linda; Horstmann, Gernot
Perceiving other people's direct gaze is important for many areas of everyday activity. For horizontal and vertical eye movements, the area of being looked at, known as the cone of gaze, has been well explored. Previous research has shown a range of eye rotations (up to eccentricities of 4°–9°) that people accept as direct gaze. Vergence is an important cue for perceiving the depth of fixation. This study examines the range of vergence angles that support the perception of being looked at. In two experiments, observers adjusted the degree of vergence of the lookers' eyes until they felt just (not) looked at. The first experiment also asked to adjust the point of being exactly looked at, which was 0° (parallel eyes). The thresholds of being just (not) looked at were around 4.5° of convergence and 2.5° divergence, which results in a depth of 7° of vergence. This depth was replicated in Experiment 2, while the thresholds of convergence (3.5°) and divergence (3.5°) slightly differ from Experiment 1. The results indicate a consistent area of vergences being accepted as direct gaze, yielding first-time evidence for a third dimension—the depth dimension—of direct gaze.